Seasonal variation in the population structure of the freshwater prawn Macrobrachium brasiliense (Decapoda: Palaemonidae) in a neotropical region - Nogueira, Caio Santos [UNESP]; Alves, Douglas Fernandes Rodrigues; Costa, Rogerio Caetano [UNESP]; Almeida, Ariadine Cristine (Soc Brasileira Carcinologia, 2021)
The present study aims to describe the population structure of the freshwater prawn Macrobrachium brasiliense and to analyze whether it varies seasonally, with emphasis on abundance variation by demographic category, sex ratio, size, and morphotypes, in addition to analyzing the recruitment period and its relationship with rainfall. The collections of M. brasiliense were carried out in a Cerrado region, in the southeastern region of Brazil. The population structure was analyzed according to the size, sex, and life stage. The density of morphotypes was calculated by the proportion of each morphotype in the population. Male and female prawns were more abundant in the largest and smallest size classes, respectively. The juvenile morphotype was the most abundant among males (45.9 %), while the Mirim and Acu morphotypes occurred in a similar proportion (27.87 % and 26.23 %, respectively). The population structure varied significantly between seasons (dry and rainy). A relationship of juvenile abundance with rainfall was recorded. The recruitment period was observed between the end of the rainy season and the beginning of the dry season, while adults were more abundant at the end of the dry season and the beginning of the rainy season. The information in this study contributes to the knowledge of the influence of seasonality and rainfall on populations of aquatic organisms in the Cerrado region, such as the prawn M. brasiliense. Rainfall seasonality affects the population structure of these organisms between seasons, possibly due to the top-down and bottom-up effects caused by different rates of nutrient input in such aquatic systems.
Keywords: Bottom-up; Caridea; recruitment; seasonality; top-down